Incorporating patient preferences into osteoarthritis treatment - Yeşim Gökçe Kutsal; Sibel Eyigör; Sevilay Karahan; Rezzan Günaydın; Jale İrdesel and Merih Sarıdoğan and Pınar Borman and Aylin Sarı and Kutay Ordu Gökkaya and Vildan Binay Safer (Archives of Rheumatology, 2021)
Objectives: This study aims to identify the relationship between treatment modalities and the patients’ preferences in osteoarthritis (OA) treatment and identify the related factors. Patients and methods: This multi-center, cross-sectional study included a total of 305 patients with OA (66 males, 239 females; mean age: 66.4±9.7 years; range, 38 to 90 years) between July 2019 and January 2020. Data including demographic and clinical characteristics of the patients were recorded using a structured questionnaire. Results: The mostly common involvement sites were knee joints, lumbar, and cervical regions, respectively. Prior to the study, the treatment modalities which were prescribed to patients were oral drugs (79.7%), topical drugs (73.8%), home-based exercise program (62.6%), and physical therapy (outpatient) (61.3%). Of the recommended remedy, 89.2% were prescribed by physiatrists, 24.6% by orthopedists, 5.6% by family practitioners, 2.6% by neurosurgeons, and 1.6% by algologists. The most beneficial treatments (to whom) were inpatient physical therapy program (47%), oral drugs (41%), home-based exercise programs (24.9%) according to patients’ perspective. According to patient preferences, nearly half of the patients preferred outpatient physical therapy program (45.9%), oral drugs (33.1%), inpatient physical therapy (20%), and home-based exercises (18%). The most common reasons for their preferences were previous benefits from treatment (54.4%), long-term effects (38%), easy access to treatment (33.1%) and concerns about side effects (28.9%). The mostly common reasons for their preferences were previous benefits from the treatment (54.4%), long-term positive effects of physical therapy (38%), easy access to the treatment (33.1%) and concerns about side effects of drugs (28.9%). Conclusion: Besides medical regimen, the results of this study showed that the patients preferred outpatient and inpatient physical therapy modalities, and home-based exercises programs. In the light of these findings, initiation of a new prescription (e.g., drugs or physical therapy modalities) in OA patients, previous treatment modalities, and approaches are suggested to be carefully reviewed by the clinician to anticipate and improve the adherence behavior to the new treatment.